How do you simplify #4sqrt(5/6) - sqrt(3/10)#?

1 Answer
Sep 2, 2016

Answer:

#4 sqrt(5/6) - sqrt(3/10) = 17/30 sqrt(30)#

Explanation:

#4 sqrt(5/6) - sqrt(3/10) = 4 sqrt((5*6)/6^2)-sqrt((3*10)/10^2)#

#color(white)(4 sqrt(5/6) - sqrt(3/10)) = 4 sqrt(30/6^2)-sqrt(30/10^2)#

#color(white)(4 sqrt(5/6) - sqrt(3/10)) = 4 sqrt(30)/sqrt(6^2)-sqrt(30)/sqrt(10^2)#

#color(white)(4 sqrt(5/6) - sqrt(3/10)) = 4/6 sqrt(30)-1/10 sqrt(30)#

#color(white)(4 sqrt(5/6) - sqrt(3/10)) = (2/3 - 1/10) sqrt(30)#

#color(white)(4 sqrt(5/6) - sqrt(3/10)) = (20/30 - 3/30) sqrt(30)#

#color(white)(4 sqrt(5/6) - sqrt(3/10)) = 17/30 sqrt(30)#